Pengaruh Electronic Word of Mouth dan Persepsi Konsumen Terhadap Keputusan Pembelian di HOS of Shopaholic Kota Malang - Andrea Dennise Gusti Nugraheni; Fullchis Nurtjahjani; Rizky Kurniawan Murtiyanto (Indo Publishing, 2026)
Electronic word of mouth and consumer perception are important factors influencing consumer purchasing decisions, which determine product sales success and business sustainability. Based on preliminary observations, HOS of Shopaholic in Malang experienced sales fluctuations and has not fully optimized its electronic word of mouth activities, yet the influence of these factors on purchasing decisions remains unclear. This study aims to analyze the effect of electronic word of mouth and consumer perception on purchasing decisions at HOS of Shopaholic Malang. Using a quantitative approach with an explanatory research design, data were collected through questionnaires distributed to 100 respondents selected by purposive sampling. The data were analyzed using multiple linear regression, coefficient of determination, and hypothesis testing through partial (t-test) and simultaneous (F-test). The results showed that electronic word of mouth partially has a positive and significant effect on purchasing decisions, consumer perception partially has a positive and significant effect on purchasing decisions, and both variables simultaneously have a positive and significant effect on purchasing decisions. The coefficient of determination (R²) of 0.433 indicates that both variables contribute 43.3% to purchasing decisions, while the remaining 56.7% is influenced by other variables. These findings confirm the importance of maintaining positive consumer perceptions and optimizing electronic word-of-mouth strategies to enhance consumer purchasing decisions.